Aspect-oriented middleware framework for resolving service discovery issues in Internet of Things. (2016) - Balakrishnan, Senthil Murugan; Sangaiah, Arun Kumar
Internet of Things (IoT) is a model of future internet and pervasive computing which have its own challenges derived from the internet in terms of scalability, undefined topology and so on. The proposed work aims to resolve the challenges posed by IoT in service discovery functionality. Considering the pervasive and context dependent nature of IoT the planned work bases its development strategy using an aspect oriented software development methodology. The novelty lies in achieving high degree configuration and customisability by selecting subset of middleware functionality depending on the need. The performance is compared with MUSIC pervasive computing middleware and Android built-in configuration. The result reveals 6.5% decrease on average boot up and reconfiguration time for smart phones and 11.6% percentage decrease in Android tablets. In the context of boot up and reconfiguration time the middleware brings out 5% decrease for smart phones and 3% for Android tablets when compared with MUSIC middleware. The middleware shows 6.3% and 4% reduction in execution time of applications on smart phones and tablets when assessed with MUSIC middleware.